Updates on MR-Guided Focused Ultrasound for Symptomatic Uterine Fibroids - Sridhar, Divya; Kohi, Maureen P. (Seminars in Interventional Radiology, 2018)
Magnetic-resonance–guided focused ultrasound (MRgFUS), also called high-intensity focused ultrasound (HIFU) is an effective, noninvasive uterine-preserving treatment for symptomatic uterine fibroids. As the use of this therapeutic modality is not yet widespread, it may remain unfamiliar to many interventional radiologists. The purpose of this review is to discuss MRgFUS, including technology, patient selection, technique, outcomes, complications, and recent data on fertility and comparative effectiveness.
Keywords: High-intensity focused ultrasound; fibroids; menorrhagia; interventional radiology